FUNGSI PENDIDIKAN ISLAM DALAM HIDUP DAN KEHIDUPAN MANUSIA (Manusia yang Memiliki Fitrah/Potensi dan sebagai Makhluk yang harus Dididik/Mendidik) - Wahyuddin, Wahyuddin (Inspiratif Pendidikan, 2016)
Abstract: The most interesting studies in the philosophy of Islamic education is about people because of its unique personality and human nature itself is difficult to understand. Knowledge of human nature was necessary to help people get to know himself who delivered the real happiness. But these efforts failed, because people only know him at the boundaries of the instrument and not on the substance. Ignorance of human nature itself as a whole due to the limitations of human knowledge about him, especially in revealing spiritual things that are abstract. This limitation due to three factors: First, in the history of human life, he was more interested in investigating natural materials (concrete), than things that are immaterial (abstract). Secondly, the limitations of human reason are only able to think about things that are instrumental rather than things that are substantial and complex. Third, the complexity and unique human problems.